(untitled) (JBN (Jurnal Bedah Nasional), 2026)
Aim: ERAS protocol has emerged as a transformative approach to perioperative care in colorectal cancer surgery in which postoperative morbidity remains significant. By integrating evidence-based interventions, ERAS protocol accelerates patients’ recovery and reduces surgical morbidity, which in turn shortens patients’ length of hospital stay. This literature review evaluates current evidence regarding the impact of ERAS implementation on postoperative outcomes in patients undergoing colorectal cancer resections. Methods: A narrative literature review was conducted using recent studies published within the last 10 years. Studies evaluating ERAS implementation in colorectal cancer resections and reporting outcomes such as post-operative complications, length of stay, and patient’s functional recovery were included. Results: Across the reviewed literature, ERAS protocols consistently demonstrated improvements in multiple postoperative outcomes. Most studies reported a significant reduction in over 90% for minimal and moderate complications. ERAS also consistently shortens hospital length of stay, particularly through early nasogastric tube removal and optimized perioperative fluid and dietary management. Early mobilization and structured recovery components improve postoperative functional recovery, supporting a faster return to preoperative activity levels. Conclusion: The ERAS protocol integrates multiple evidence-based interventions that collectively reduce operative stress and enhance patient recovery. Current evidence demonstrates that ERAS implementation significantly decreases postoperative complications and shortens hospital length of stay, while also offering a cost-effective approach to perioperative management.